Recurrence of atrial fibrillation within three months after pulmonary vein isolation for patients with paroxysmal atrial fibrillation: Analysis using external loop recorder with auto‐trigger function. Issue 2 (20th September 2014) - Kawasaki, Shiro; Tanno, Kaoru; Ochi, Akinori; Inokuchi, Koichiro; Chiba, Yuta; Onishi, Yoshimi; Onuma, Yoshimasa; Munetsugu, Yumi; Kikuchi, Miwa; Ito, Hiroyuki; Onuki, Tatsuya; Miyoshi, Fumito; et al.
Abstract: Background: Pulmonary vein isolation (PVI) via catheter ablation has been shown to be a highly effective treatment option for patients with symptomatic paroxysmal atrial fibrillation (AF). The recurrence of AF within 3 months after PVI is not considered to be the result of ablation procedure failure, because early recurrence of AF is not always associated with late recurrence. We examined the usefulness of an external loop recorder with an auto‐trigger function (ELR‐AUTO) for the detection of atrial fibrillation following PVI to characterize early recurrence and to determine the implications of AF occurrence within 3 months after PVI. Methods: Fifty‐three consecutive symptomatic patients with paroxysmal AF (age 61.6±12.6 years, 77% male) who underwent PVI and were fitted with ELR‐AUTO for 7±2.0 days within 3 months after PVI were enrolled in this study. Results: Of the 33 (62.2%) patients who did not have AF recurrence within 3 months after PVI, only 1 patient experienced AF recurrence at 12 months. Seven (35%) of the 20 patients who experienced AF within 3 months of PVI experienced symptomatic AF recurrence at 12 months. The sensitivity, specificity, positive predictive value, and negative predictive value of early AF recurrence for late recurrence were 87.5%, 71.1%, 35.0%, and 96.9%, respectively. Conclusions: AF recurrence measured by ELR‐AUTO within 3 months after PVI can predict the late recurrence of AF. Freedom from AF in the first 3 months following ablation significantly predicts long‐term AF freedom. ELR‐AUTO is useful for the detection of symptomatic and asymptomatic AF.